2013
DOI: 10.1242/dev.080499
|View full text |Cite
|
Sign up to set email alerts
|

Specialized progenitors and regeneration

Abstract: SummaryPlanarians are flatworms capable of regenerating all body parts. Planarian regeneration requires neoblasts, a population of dividing cells that has been studied for over a century. Neoblast progeny generate new cells of blastemas, which are the regenerative outgrowths at wounds. If the neoblasts comprise a uniform population of cells during regeneration (e.g. they are all uncommitted and pluripotent), then specialization of new cell types should occur in multipotent, non-dividing neoblast progeny cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
91
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 59 publications
4
91
0
2
Order By: Relevance
“…Also, transient structures like the blastema are not always useful for comparative studies across distant taxa. Where blastemas can be characterized by a mass of cells clustering in the area of the wound after closure, leading to growth and regeneration into new organs or new body parts, it has been shown that the histological nature of this mass of cells is different in different regenerative structures (Shibata et al, 1999;Cebrià et al, 2002;Bosch et al, 2008;Kragl et al, 2009;Wenemoser and Reddien, 2010;Aboobaker, 2011;Reddien, 2013;Bely et al, 2014). Additionally in some epimorphic regenerative events, i.e., where local stimulation of cell proliferation precedes the development of the new part, there is a lack of structures that resemble a blastema, such as during the Ciona intestinalis siphon regeneration (Auger et al, 2010) or the whole body regeneration in colonial ascidians (Brown et al, 2009b).…”
Section: Resultsmentioning
confidence: 99%
“…Also, transient structures like the blastema are not always useful for comparative studies across distant taxa. Where blastemas can be characterized by a mass of cells clustering in the area of the wound after closure, leading to growth and regeneration into new organs or new body parts, it has been shown that the histological nature of this mass of cells is different in different regenerative structures (Shibata et al, 1999;Cebrià et al, 2002;Bosch et al, 2008;Kragl et al, 2009;Wenemoser and Reddien, 2010;Aboobaker, 2011;Reddien, 2013;Bely et al, 2014). Additionally in some epimorphic regenerative events, i.e., where local stimulation of cell proliferation precedes the development of the new part, there is a lack of structures that resemble a blastema, such as during the Ciona intestinalis siphon regeneration (Auger et al, 2010) or the whole body regeneration in colonial ascidians (Brown et al, 2009b).…”
Section: Resultsmentioning
confidence: 99%
“…S4C; Table S1). Although we cannot specify the cell types that contribute to the gradient, we observed nuclear localization of β-CATENIN-1 in sub-epidermal muscular cells, which are the source of positional information cues (Witchley et al, 2013) and in proliferating cells, which correspond to neoblast and early progeny stem cells (Reddien, 2013) (Fig. S4D).…”
Section: Introductionmentioning
confidence: 95%
“…On the basis of elegant single cell transplantation studies in lethally irradiated planarians (Wagner et al, 2011), it has been estimated that less than 5% of the planarian stem cells are truly pluripotent (Rink, 2013). Therefore, we and others hypothesize that a fraction of the heterogeneous stem cell pool may be comprised of lineage-committed or specialized progenitor cells (Reddien, 2013). To fully understand the mechanisms underlying how neuronal diversity is maintained or reestablished in planarians it will be essential to define any neural precursor populations that may exist.…”
mentioning
confidence: 97%